2011
DOI: 10.1111/j.1440-1827.2011.02670.x
|View full text |Cite
|
Sign up to set email alerts
|

Pyloric gland metaplasia/differentiation in multiple organ systems in a patient with Peutz–Jegher's syndrome

Abstract: Peutz-Jegher's syndrome (PJS) involves multiple organ systems and the development of hamartomatous, metaplastic, or neoplastic lesions of different cell lineages. Among them, glandular lesions are the most common, but their properties are obscure. We report here a 53-year-old woman with PJS who developed multiple hamartomatous polyps in the jejunum and mucinous glandular lesions in multiple organ systems: glandular metaplasia in the urinary bladder; lobular endocervical glandular hyperplasia in the uterine cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…Minimal deviation adenocarcinoma (an extremely well differentiated form of gastric type adenocarcinoma) of the cervix and ovarian sex cord tumor with annular tubules are the most well-known tumors of the female genital organs associated with PJS, but association with ovarian mucinous tumors has rarely been described [4]. Moreover, gastric phenotype of the mucinous epithelium in patients with PJS has not been clearly determined, and there is only one case briefly mentioning ovarian mucinous tumor with pyloric/gastric differentiation [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Minimal deviation adenocarcinoma (an extremely well differentiated form of gastric type adenocarcinoma) of the cervix and ovarian sex cord tumor with annular tubules are the most well-known tumors of the female genital organs associated with PJS, but association with ovarian mucinous tumors has rarely been described [4]. Moreover, gastric phenotype of the mucinous epithelium in patients with PJS has not been clearly determined, and there is only one case briefly mentioning ovarian mucinous tumor with pyloric/gastric differentiation [4].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, gastric phenotype of the mucinous epithelium in patients with PJS has not been clearly determined, and there is only one case briefly mentioning ovarian mucinous tumor with pyloric/gastric differentiation [4]. In that case report, the pyloric gland differentiation involved the lesions of multiple organs, including the jejunum, urinary bladder, uterine cervix, fallopian tube, and ovary.…”
Section: Discussionmentioning
confidence: 99%
“…One possible exception to this generalization is in the context of mucinous lesions, as rare primary mucinous epithelial alterations of the tubal mucosa, ranging from simple mucinous metaplasia to benign and borderline‐like neoplasia, have been reported. Some of these cases have been associated with multifocal mucinous neoplasia within the gynaecological tract or have occurred in patients with Peutz–Jegher’s syndrome 34–40 . Recently, Wong et al.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these cases have been associated with multifocal mucinous neoplasia within the gynaecological tract or have occurred in patients with Peutz-Jegher's syndrome. [34][35][36][37][38][39][40] Recently, Wong et al 41 reported a series of 23 mucinous epithelial lesions of the Fallopian tubes and considered that these represented an in-situ (metaplastic) process rather than mucosal colonization from an extratubal site. This interpretation was supported by the lack of cellular atypia and the absence in most cases of an E112 C J R Stewart et al…”
Section: Fallopian Tube Metastases E111mentioning
confidence: 99%
“…Therefore, this case is representative of SMMN-FGT, since the gastric-type mucinous lesions were identified in the cervix and in the fallopian tube. Furthermore, SMMN-FGT lesions frequently occur in women with PJS [15].…”
Section: Pathological Findingsmentioning
confidence: 99%